2006
DOI: 10.1007/s11010-006-9161-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological basis for effect of physical conditioning on chronic ethanol-induced hypertension in a rat model

Abstract: The study aim was to investigate the interaction of physical conditioning and chronic ethanol ingestion on blood pressure (BP), heart rate (HR), nitric oxide (NO) and oxidants/antioxidants balance in the plasma of rats. Male Fisher rats were divided into four groups of seven animals each and treated as follows: (1) Control (5% sucrose, orally) daily for 12 weeks; (2) ethanol (4 g kg(-1), orally) daily for 12 weeks; (3) exercise training on treadmill plus sucrose daily for 12 weeks and (4) exercise training on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
2
8
1
Order By: Relevance
“…The magnitude of the increase in blood pressure in heavy drinkers averages about 5 to 10 mmHg, with systolic increases nearly always greater than diastolic increases [18] . Similar changes in blood pressure were also reported in preclinical studies [19][20][21][22] . In the Framingham cohort [23,24] , there was an increase of 7 mmHg in mean arterial pressure when heavy alcohol users were compared with all others.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…The magnitude of the increase in blood pressure in heavy drinkers averages about 5 to 10 mmHg, with systolic increases nearly always greater than diastolic increases [18] . Similar changes in blood pressure were also reported in preclinical studies [19][20][21][22] . In the Framingham cohort [23,24] , there was an increase of 7 mmHg in mean arterial pressure when heavy alcohol users were compared with all others.…”
Section: Introductionsupporting
confidence: 85%
“…In the endothelium, depletion of NO production or NO reaction with superoxide anion to form toxic peroxynitrite radical which causes endothelial injury, impairment and hypertension in alcohol treated rats [20][21][22]62,80,94] . Recent studies have shown that chronic ethanol ingestion induces hypertension which was related to increased aortic inflammation, elevated angiotensin II levels, induction of NADPH oxidase causing endothelial injury, depletion of antioxidants, down-regulation of endothelial NO generating system and impaired vascular relaxation in rats [6,[19][20][21][22]62,80] . This mechanism is most likely implicated in chronic alcohol-induced hypertension.…”
Section: Endothelium and Oxidative Stress In Alcohol-induced Hypertenmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the superoxide ions were significantly high due to antioxidant enzyme inhibition. The superoxide ions are able to interact with NO (nitric oxide) to form peroxynitrate which has a wider range of free radical potentials [13]. So, in summary, ethanol performs as an oxidative stress inducer which is the principal cause of hypertension.…”
Section: Alcohol Induction Of Ros Productionmentioning
confidence: 99%